Effect of Helicobacter pylori and its eradication on gastric juice ascorbic acid. Issue 3 (March 1994) - Banerjee, S; Hawksby, C; Miller, S; Dahill, S; Beattie, A D; McColl, K E
Abstract : The presence of ascorbic acid in gastric juice may protect against gastric carcinoma and peptic ulceration. This study examined the effect of Helicobacter pylori (H pylori) on the secretion of ascorbic acid into gastric juice by measuring fasting plasma and gastric juice ascorbic acid concentrations in patients with and without the infection and also before and after its eradication. Gastric juice ascorbic acid concentrations in 19 H pylori positive patients were significantly lower (median 2.8, range 0-28.8 micrograms/ml) than those in 10 H pylori negative controls (median 17.8, range 5.6-155.4 micrograms/ml) (p < 0.0005) despite similar plasma ascorbic acid concentrations in both groups. The median gastric juice:plasma ascorbic acid ratio in the H pylori positive patients was only 1.16 (range 0.02-6.67), compared with a median ratio of 4.87 (range 0.76-21.33) in H pylori negative controls (p < 0.01). In the patients with H pylori infection there was a significant negative correlation between the severity of the antral polymorphonuclear infiltrate and gastric juice ascorbic acid concentrations (correlation coefficient -0.52, p = 0.02). After eradication of H pylori in 11 patients, gastric juice ascorbic acid concentrations rose from 2.4 (0-12.8 micrograms/ml) to 11.2 (0-50 micrograms/ml) (p = 0.01). The median gastric juice: plasma ascorbic acid ratio also increased from 1.33 (0.05-6.67) to 2.89 (0.01-166) (p = 0.01). In conclusion, the high gastric juice:plasma ascorbic acid ratio in H pylori negative subjects shows active secretion of ascorbic acid into gastric juice. Secondly, H pylori infection causes a reversible lowering of gastric juice ascorbic acid concentrations, which may predispose to gastric carcinoma and peptic ulceration.